La vulnérabilité cumulative face aux défis socio-environnementaux en Côte d’Ivoire - Jeremy Allouche; Dieunedort Wandji (VertigO)
Based on theories in political ecology, this paper develops the notion of cumulative vulnerability in order to highlight the underpinning social and structural drivers. This notion allows us to challenge the causal, sectoral and disciplinary approach that dominate academic studies on the concept of vulnerability. We use the cases of Grand Lahou and Abidjan, in order to illustrate this approach.